Evaluation of Sound Velocity and Interaction Study in Binary Liquid Mixtures - Saxena, M.C.; Tripathi, Ashutosh (Asian Journal of Chemistry, 2010)
Sound velocities have been predicted in the binary liquid mixtures of cyclohexane-benzene, cyclohexane-toluene and cyclohexane- p-xylene at 30°C in the light of ideal mixing and Nomoto's relations. The relative merits of both relations have been assessed.